CURRENT ISSUES OF EVIDENCE AND PROOF IN ECONOMIC PROCEDURAL LAW - Netska, Liubov; Dyachyshyn, Mariia (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2023)
Goal: the purpose of the scientific article is to generalize modern scientific and practical approaches to solving problematic issues regarding evidence and proof in the economic process, as well as to form guidelines for eliminating or overcoming obstacles to the proper use of evidence during the exercise of the right to defense in the economic court. Research methods: general (theoretical and complex) and special research methods (system analysis and structural-functional analysis, formal-logical, comparative) were used. Results: the researched features of evidence and proof in the business process will allow further improvement and simplification of the process of proof, identify gaps in legal regulation in this area and shortcomings of current legislation, as well as positive developments in judicial practice. Discussion: it is emphasized that the economic court evaluates the evidence according to its internal conviction, which is based on a comprehensive, complete and objective consideration in the judicial process of all the circumstances of the case in their totality, guided by the law. It is emphasized that the evaluation of evidence is a mental, logical activity that leads to conclusions about the admissibility, propriety, reliability and plausibility of each piece of evidence in the case for the subsequent formulation of conclusions and decision-making. It is seen that the evaluation of evidence by the court allows to gradually form unified approaches to: a) understanding/perception of certain data as evidence, b) weighted balancing when the court establishes the advantages of some evidence over others, c) the process of proof as a consistent and necessary algorithm of actions in each category of cases. It is claimed that the emergence of new types of evidence and means of proof provides new opportunities for protection for the parties to economic litigation, but also creates difficulties in the conditions of imperfect legislation, insufficiently formed and contradictory economic and judicial practice.